Analisa Kinerja Simpang Tak Bersinyal di Jalan Mertojoyo-Jalan Joyo Utomo, Kelurahan Merjosari Kota Malang - Garung, Yovanus Hendradino; Arifianto, Andy Kristafi ; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Intersection is one part of the road that is the area where traffic conflicts occur. The existence of this conflict will result in interference with the movement of the vehicle. This situation is generally known as traffic flow congestion. Geometric condition of unmarked intersection on Mertojoyo - Joyo Utomo roads of Merjosari village Malang city, conflicts often occur which are caused by the approaching width which is less proportional to the current of the vehicle, so it is necessary to analyze. The purpose of this study is to determine the size of the intersection capacity, intersection performance and alternative intersection improvement directions. The method used in analyzing this perverse performance refers to the Indonesian highway Capacity Manual 1997 (MKJI 1997). To analyze this crossing, the average traffic data collected during 12 working days is taken. Based on the recapitulation of traffic volume for 12 working days, the highest QTotal was 2994 smp/hour which occurred on Saturday period 17.00 - 18.00. Based on the results of data analysis of traffic flow on a busy Saturday, the period 17.15-18.15, obtained QTotal = 2994 Smp / Hour, capacity value (C) = 2135.98 smp/hour the degree of saturation (DS) = 1.381 > 0.75 values suggested MKJI 1997. Alternative installation of prohibited traffic signs turn right on the main road, C = 2693,829 smp/hour, degree of saturation (DS) = 1,112 > 0,75. Alternative widening on main roads and minor roads and the installation of prohibited traffic signs turn right on the main road, obtained C = 3178,378 smp/hour, DS = 0,94 > 0,75. Alternative two-phase signaling and widening on the main road and minor road, the capacity of each approach < 0.75 is obtained, thus overcoming the problem at this intersection.